Changes in Soluble Sugars, Sugar Profile, Starch and Proline in Developing Coconut (Cocos nucifera L.) Inflorescences - H. D. D. Bandupriya; L. K. Weerakoon; C. S. Ranasinghe; W. P. K. K. Fernando (International Coconut Community Journal, 2008)
Changes in soluble sugars, sugars profile, starch and proline levels in inflorescence rachillae from individual coconut palms were investigated during inflorescence development with the aim of determining a possible correlation between these characters and morphogenic potential of inflorescence tissues. Rachillae for analysis were collected from unopened inflorescences of -1 to -13 stages (considering the youngest open inflorescence as 0 stage) in decreasing order of maturity (–1 stage is the most mature stage whereas –13 is the most immature stage). Important differences among the maturity stages were observed for total sugars. In very tender inflorescences (-13 and -12), the total sugar content was very low whereas a gradual increase was observed from -11 to -7 stages, with -7 stage having the highest level. The total sugar content in more mature inflorescences was relatively low, with the exception of -2 stage, which had a high total sugar content. In regard to sugar profiles, sucrose, fructose and glucose were the main soluble sugars present in coconut inflorescence and sucrose was the most abundant sugar in -5 to -9 maturity stages. Total soluble sugars and sucrose in maturity stages from -5 to -9 showed a very similar variation and significantly higher levels of sucrose were observed in -6 to -8 stages. The proline content in the mature stages, -1 to –3, was significantly lower than in the other stages with no significant variation in the stages –4 to –11. The pattern of variation in starch content was similar to that of proline which decreased with increasing maturity of inflorescence. In view of the results obtained, the higher accumulation of sucrose and total sugars in -6, -7 and -8 stages may have some significance in morphogenesis, especially as an energy source. The 10 cm length inflorescence that responds better for callusing falls within this range. Thus total sugar and sucrose content may be possible biochemical markers for assessing the morphogenic potential of inflorescence explants.